2022
DOI: 10.1177/00197939221093562
|View full text |Cite
|
Sign up to set email alerts
|

Firm Pay Policies and the Gender Earnings Gap: The Mediating Role of Marital and Family Status

Abstract: Using data from the Canadian Employer-Employee Dynamics Database between 2001 and 2015, the authors examine the impact of firms’ hiring and pay-setting policies on the gender earnings gap in Canada. Consistent with the existing literature and following Card, Cardoso, and Kline (2016), findings show that firm-specific premiums explain nearly one-quarter of the 26.8% average earnings gap between female and male workers. On average, firms’ hiring practices, due to differences in the relative proportion of women h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This article examines the most significant factor affecting people's perceptions of the gender wage gap. From the previous articles that have been reviewed (Sipe et al, 2016;Töpfer, 2020;Li et al,2023;Foote & Harmon, 2006;Khitarishvili, 2019), this paper was able to come to the conclusion that five demographic variables were able to be connected different hypotheses. These are the five hypotheses that will be brought up throughout this article:…”
Section: Development Of Hypothesismentioning
confidence: 85%
“…This article examines the most significant factor affecting people's perceptions of the gender wage gap. From the previous articles that have been reviewed (Sipe et al, 2016;Töpfer, 2020;Li et al,2023;Foote & Harmon, 2006;Khitarishvili, 2019), this paper was able to come to the conclusion that five demographic variables were able to be connected different hypotheses. These are the five hypotheses that will be brought up throughout this article:…”
Section: Development Of Hypothesismentioning
confidence: 85%
“…Jewell et al (2019) find firm-level sorting accounts for three times as much of the gender pay gap as occupational sorting using employer–employee data in the United Kingdom, but after adjusting for worker characteristics this was only equal to about 6% of the unexplained gap. More recently, Li et al (2022) replicated Card et al 2016's study design using the Canadian Employer–Employee Dynamics Database and found that about a quarter of the wage gap could be explained by firm pay premiums, with nearly half of this difference attributable to firm-level sorting. While these and other studies 2 draw attention to the importance of firm-level segregation, the varied national contexts are difficult to extrapolate to the United States given the different labor market structures.…”
Section: Bringing the Firm Back In (Again)mentioning
confidence: 89%
“…This devaluation hypothesis stands in contrast to economic accounts of firm segregation (Card et al, 2016;Li et al, 2022) in which wage differences between firms generally reflect firms' surpluses and thus exist independent of workforce gender composition. In economic accounts, women are underrepresented at the highest paying firms, and this may reflect employers' preference for male employees at the time of hire (allocative discrimination), but could also reflect women's self-selection into lower-paying firms, perhaps due to compensating differentials.…”
mentioning
confidence: 79%
“…The Li et al (2023) inspected the impact of employers' recruiting and pay-setting strategies on the gender earnings gap in Canada using data from the Canadian Employer-Employee Dynamics Database between 2001 and 2015. Findings support Card, Cardoso, and Kline (2016) and the body of previous data by demonstrating that approximately onequarter of the 26.8% average earnings discrepancy between male and female workers may be attributed to firm-specific premiums.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%